Sociolinguistic Approach in Teaching Arabic: A Literature Review - Zaenal Rafli; Muhammad Afif; Biqi Zain (Institut Studi Islam Muhammadiyah Pacitan, 2026)
The sociolinguistic approach has gained increasing attention in the field of Arabic language teaching as educators recognize the inseparable relationship between language, society, and culture. Arabic, as a language characterized by diglossia, dialectal variation, and strong cultural embeddedness, presents unique pedagogical challenges and opportunities. This literature review aims to examine key theoretical foundations, empirical findings, and pedagogical implications of applying a sociolinguistic approach in teaching Arabic. The review synthesizes studies on Arabic diglossia, language variation, pragmatic competence, classroom interaction, and identity construction in Arabic learning contexts. Findings indicate that sociolinguistically informed instruction enhances learners’ communicative competence, pragmatic awareness, and cultural literacy, while also addressing the gap between Modern Standard Arabic and spoken varieties. However, challenges remain regarding curriculum design, teacher preparedness, and assessment practices. This review concludes that integrating sociolinguistic principles into Arabic pedagogy is essential for developing contextually appropriate, communicative, and culturally responsive Arabic language instruction.